The Role of Some Hormone Levels and Histopathological Changes in Thyroid Gland and Testes in Experimentally Induced Myocardial Infraction in Male Rats - Noori Mohammed Luaibi (Journal of Global Pharma Technology, 2017)
Acute myocardial infarction is a common cardiac emergency, with the potential for substantial morbidity and mortality. Myocardial infarction occurs when myocardial ischemia, a diminished blood supply to the heart, exceeds a critical threshold and overwhelms myocardial cellular repair mechanisms designed to maintain normal operating function and homeostasis. The aim of the current study was to evaluate the alterations in hormone concentrations TSH, T3, T4, and testosterone in experimental rats has been induced for myocardial infarction. According to statistical analysis revealed that the levels of T3, T4 and testosterone were decreased in comparison with healthy control group and the decreasing value of these hormones were continuing to occur especially in 7 and 14 days after myocardial infarction occurs .While the levels of TSH illustrated increment in various periods of time used in this study after admission of myocardial infarction, in addition to histological changes that had occurred in thyroid and testes sections. Thyroid sections showed follicles empty from colloid and degenerative changes in thyroid follicular cells in long period of time after acute myocardial infarction, while testes showed immaturity of spermatogonial cells with deformed sperms inside the lumen.Keywords: Myocardial infarction, TSH, T3, T4, Testosterone.